Inclusive Practices Outside of the United States: A Scoping Literature Review - Eric J. Anderson; Emily Oehrtman; Elizabeth K. Cohara (MDPI AG, 2024)
Regardless of differences in abilities, background, or citizenship, students have a right to effective education alongside their peers who do not have disabilities. For many students with disabilities (especially students with more significant support needs), education is something that happens outside of the general education classroom, which limits their access to the academic and social benefits of inclusive education. Fortunately, advocates, educators, and researchers are working to ensure that more students can access inclusive classrooms. Much is known about these practices within the United States, but less research focuses on inclusion in other nations and regions. This scoping literature review synthesizes intervention research conducted outside of the United States and summarizes data from 15 studies representing seven countries and including 42 total student participants. Key findings highlight important outcomes (e.g., academic engagement and communication) and effective methods (e.g., embedded instruction and peer supports) being used around the world to support students with intellectual and developmental disabilities.